Shakespeare and Renaissance Literature before Heterosexuality - Bach, R. author. aut Link
XII, 248 p.
Keywords: Shakespeare has been misread for centuries as having modern ideas about sex and gender.This book shows how in the Restoration and Eighteenth century, Shakespeare's plays and other Renaissance texts were adapted to make them conform to these modern ideas.Through readings of Shakespearean texts, including King Lear, Antony and Cleopatra, and Othello, and other Renaissance drama, the book reveals a sexual world before heterosexuality. Shakespeare and Renaissance Literature Before Heterosexuality shows how revisions and criticism of Renaissance drama contributed to the emergence of heterosexuality.It also shows how changing ideas about status, adultery, friendship, and race were factors in that emergence.